Pengaruh Model Pembelajaran Bersiklus Terhadap Motivasi Belajar Pendidikan Agama Kristen Dan Budi Pekerti Siswa Kelas XI SMA Negeri 1 Tampahan Tahun Pembelajaran 2023/2024 - Exaudi Dian Mayawie Napitupulu; Goklas J. Manalu; Frainskoy Rio Naibaho; Wilson Simanjuntak; Taripar Aripin Samosir (Jurnal Teologi Injili dan Pendidikan Agama, 2023)
This research aims to determine the effect of the cyclical learning model on PAK learning motivation and character of class XI students at SMA Negeri 1 Tampahan in the 2023/2024 academic year. The hypothesis of this research is that there is a positive and significant influence in the use of the cyclical learning model on the PAK learning motivation and character of class XI students at SMA Negeri 1 Tampahan for the 2023/2024 academic year. This research uses an experimental type research method with a pre-experimental research design in the form of "One Shot Case Study". The population in this study was all 30 students in class XI of SMA Negeri 1 Tampahan for the 2023/2024 academic year. Sampling in this study used a purposive sampling technique using the entire population as the research sample, namely 30 students in class XI SMA Negeri 1 Tampahan for the 2023/2024 academic year. This research instrument is in the form of a closed questionnaire for variable the value of ý=a+bX is ý=8.77+0.85X, and Fh > Ft (18.70 > 4.20). From the results of the value analysis, it was obtained from the hypothesis test that H0 was rejected and Ha was accepted, namely that there was a positive and significant influence between the application of the cyclical learning model and the learning motivation for Christian Religious Education and Character in class XI students of SMA Negeri 1 Tampahan for the 2023/2024 academic year.